2015
DOI: 10.3168/jds.2014-8584
|View full text |Cite
|
Sign up to set email alerts
|

Body condition score at calving affects systemic and hepatic transcriptome indicators of inflammation and nutrient metabolism in grazing dairy cows

Abstract: Calving body condition score (BCS) is an important determinant of early-lactation dry matter intake, milk yield, and disease incidence. The current study investigated the metabolic and molecular changes induced by the change in BCS. A group of cows of mixed age and breed were managed from the second half of the previous lactation to achieve mean group BCS (10-point scale) that were high (HBCS, 5.5; n=20), medium (MBCS, 4.5; n=18), or low (LBCS, 3.5; n=19). Blood was sampled at wk -4, -3, -2, 1, 3, 5, and 6 rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 48 publications
6
62
2
2
Order By: Relevance
“…Furthermore, obese cows would be more susceptible to the induction of ketosis than would cows of normal body condition. It has been recently reported that high BCS at calving were associated with greater concentrations of BHBA and upregulation of genes involved in ketogenesis in the liver during postpartum period compared to cows with low BCS at calving (Akbar et al, 2015). In the present study, ketotic cows had higher BCS at calving and during the first weeks postpartum than healthy cows, and they lost more body condition compared to the non-diseased cows.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, obese cows would be more susceptible to the induction of ketosis than would cows of normal body condition. It has been recently reported that high BCS at calving were associated with greater concentrations of BHBA and upregulation of genes involved in ketogenesis in the liver during postpartum period compared to cows with low BCS at calving (Akbar et al, 2015). In the present study, ketotic cows had higher BCS at calving and during the first weeks postpartum than healthy cows, and they lost more body condition compared to the non-diseased cows.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 59%
“…In other word, the ketotic cows had higher BCS at calving and during the first weeks postpartum than the healthy cows, and significantly lost more body condition score over a prolonged period of time compared to the non-diseased cows (Gillund et al, 2001). Recently, Akbar et al (2015) reported that cows with high BCS at calving had greater concentrations of BHBA and hepatic expression of genes related to ketogenesis postpartum compared to cows with low BCS at calving. Some herds have persistent ketosis problems caused by feeding ketogenic silages (Tveit et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, postpartum release of NEFA from adipose tissue mostly exceeds the needs and oxidation capabilities of the liver (19) and causes formation of ketone bodies including β-hydroxybutyrate (BHBA) and reesterification to triglycerides (TG). The latter are stored in hepatocytes and implicate the development of fatty liver, reduced metabolic function, health status, productivity, and reproductive performance, as well as incidence and severity of metabolic disorders and infectious diseases (2). NEB delays the start of the ovarian activity and reduces the number of oestrus cycles, extending the days open (28).…”
Section: Discussionmentioning
confidence: 99%
“…Durante el ciclo productivo la vaca lechera debe parir con una CC de 3.25 a 3.5 y no bajar a menos de 2.5 a los 60 a 90 días en leche. Si el animal pierde más de una unidad entre el parto y los 100 días en leche, verá comprometida su fertilidad (15,16) . La pérdida en CC durante el postparto es un fenómeno normal, debido a que los requerimientos son mayores a los aportes ofrecidos por la dieta y al nivel de consumo de alimento del animal.…”
Section: Conceptos Básicosunclassified
“…Estas son vacas que presentan una marcada inmunosupresión, con mayores incidencias de retención de membranas fetales, metritis, mastitis, hipocalcemia e hipomagnesemia, cetosis, desplazamientos del abomaso e hígado graso. Además son animales que se tardan más en normalizar su ciclicidad postparto, con una TC reducida y por ende una tasa de preñez disminuida (3,13,16,28,(38)(39)(40)(41)(42) .…”
Section: Conceptos Básicosunclassified